ELEMEN-ELEMEN DASAR KEJAHATAN TERHADAP KEMANUSIAAN : Basic Elements of Crimes against Humanity - Ayu Nrangwesti; Yulia Fitriliani; Maya Indrasti Notoprayitno (Jurnal Hukum PRIORIS, 2023)
This research was created to analyze the basic elements of crimes against humanity as stated in the 1998 Rome Statute. The study carried out was comprehensive (looking through the context of Indonesian criminal law, human rights law and international law), and comparative (comparing the elements of the crime of genocide). The background to the emergence of the research problem is the uncertainty of the nomenclature of crimes against humanity which includes the word humanity in it. This is because the concept of humanity can give rise to broad interpretations. This research is also motivated by the desire to compare crimes against humanity with the crime of genocide, especially those related to similar or overlapping elements. The problem in this research consists of 2 (two) main problems, namely: First, a comprehensive analytical elaboration of 3 (three) basic elements crimes against humanity; The second analytical elaboration is comparative to the crime of genocide. The aim of this research is ultimately to provide recommendations to the Indonesian government regarding input for reconceiving crimes against humanity in statutory regulations. The benefits of research are both academic (one of the duties of lecturers is conducting research and for teaching materials for international criminal law and human rights law) and practical (for practitioners, such as judges, prosecutors, lawyers, non-governmental organization activists and social/human rights observers man). This research is a type of doctrinal research with a comparative approach. The research data sources used are primary legal materials (primary sources). Apart from primary legal materials, secondary legal materials (secondary sources) are also the main sources in this research. A comparative approach is carried out by comparing the elements contained in crimes against humanity with the crime of genocide. The conclusion of this research is the discovery of 3 (three) main elements of crimes against humanity, namely: Widespread and systematic attacks; Directed attack on civilian people; Imputable to state/organization's policy. The most difficult element to prove is the third element, namely finding a connection between the actions of a person or group of people and their country's policies. The crime of genocide includes concrete and reliable elements that characterize the crime, while crimes against humanity still seem to overlap with the crime of genocide, even with other international crimes. Keywords: Genocide; Imputability; Crimes against Humanity; Widespread and Systematically Attack; Civilian.